The suitability of recycled papers for printing UHF RFID antennas - Pivar, Matej; Muck, Tadeja; Gregor Svetec, Diana (Anali PAZU, 2022)
The main goal of the research was to optimize printing conditions for printing UHF RFID antennas and from different recycled papers select the most appropriate printing substrate. In the research coated and uncoated recycled papers and conductive printing ink from two producers were analysed. UHF RFID antennas were printed using semi-automatic screen printing device. Properties of printing substrates and prints were determined with the standardized testing methods for paper and graphic products, further electrical properties and operability of UHF RFID antennas were checked. The research has confirmed, that recycled papers could be applied as printing substrates for printed electronics. Characteristics of recycled papers, which are important for good interaction with the conductive printing ink and proper functionality of printed electronics were determined.
Keywords: recycled paper; RFID antenna; screen printing; printed electronics